Content of Experimental Works on Teaching Students to Think Independently on the Base of a Competent Approach - Ilhomovna, Abdirashidova Maftuna; Usmanovna, Azimova Dilfuza (International Journal on Orange Technologies, 2023)
In the article, teaching elementary school students to think independently on the basis of a competency-based approach, independent thinking as a way of perceiving reality, is the product of the process of thinking - the highest result.